Aspotilles as the COVID-19 comes - S. Andruet, Armando (2020)
I propose in this contribution to make a brief review of some impressions that the pandemic event has given us and which we believe, that may be of interest to share them in order to develop future approaches and perspectives of the current evolution that the same process of COVID-19 disease has proposed to all of us. All these impressions are at last, the result of a great perplexity – not surely like the one that Averroes will have had – that pandemic disease has caused in the man of the 21st century and therefore not so insignificant the same as to despise them. Its result is partially the one we now share and of which, we must also warn that the reader does not seek in them a contribution of a scholarly work, judge it, as a transit at intersections that finds rootsin the anthropological, bioethic and cultural